2022
DOI: 10.1101/2022.12.19.521016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mabs, a suite of tools for gene-informed genome assembly

Abstract: Motivation: Despite constantly improving methods of genome sequencing, the task of error-free eukaryotic genome assembly is not yet solved. Among other kinds of problems of eukaryotic genome assembly are so-called "haplotypic duplications", which may manifest themselves as cases when alleles are mistakenly assembled as paralogs. Haplotypic duplications are dangerous as they create illusions of gene family expansions and, thus, may bring a scientist to wrong conclusions about genome evolution and functioning. R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…To overcome this problem, we used the tool Mabs. Mabs is an add-on to long-read assemblers that allows automatic optimization of assembly parameters (Schelkunov, 2022). The application of Mabs improved the assembly both in terms of N50 and a fraction of duplicate genes (Table 1, Supplementary Table A2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this problem, we used the tool Mabs. Mabs is an add-on to long-read assemblers that allows automatic optimization of assembly parameters (Schelkunov, 2022). The application of Mabs improved the assembly both in terms of N50 and a fraction of duplicate genes (Table 1, Supplementary Table A2).…”
Section: Resultsmentioning
confidence: 99%
“…Oxford Nanopore reads were trimmed by Porechop (Wick, n.d.). The genome of H. sosnowskyi was assembled by Mabs-hifiasm (Schelkunov, 2022), Hifiasm (Cheng et al ., 2021), Flye (Kolmogorov et al ., 2019), Miniasm (Li, 2016), and Canu (Nurk et al ., 2020). After assembly, haplotypic duplication removal was performed by Purge_dups (Guan et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that Hifiasm performed better than other assemblers; however, it produced many duplicated genes due to incomplete collapsing of haplotypes. To overcome this problem, we used the tool Mabs—an add‐on to long‐read assemblers that allows automatic optimization of assembly parameters (Schelkunov, 2023). The application of Mabs improved the assembly both in terms of N50 and a fraction of duplicate genes (Table 1, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Oxford Nanopore reads were trimmed by Porechop (Wick, n.d.). The genome of H. sosnowskyi was assembled by Mabs‐hifiasm (Schelkunov, 2023), Hifiasm (Cheng et al., 2021), Flye (Kolmogorov et al., 2019), Miniasm (Li, 2016), and Canu (Nurk et al., 2020). After assembly, haplotypic duplication removal was performed by Purge_dups (Guan et al., 2020).…”
Section: Methodsmentioning
confidence: 99%